Study of Behavioral of Vertical Irregular Building Structure by Applying Column Variation Due to Earthquake using Dynamic Analysis - Pawening Esti Pramundi; Syafwandi Syafwandi; Agyanata Tua Munthe; Agung Sumarno (IJTI International Journal of Transportation and Infrastructure eISSN 2597-4769 pISSN 2597-4734, 2022)
The development of high-rise buildings in Indonesia is now increasingly diverse. The need for increasingly narrow land functions affects the shape of the building which tends to be irregular. Irregularity in the building requires structural planners to build buildings that are safe against earthquakes but also do not forget the aspect of user comfort. In this study, an analysis of the dynamics of earthquakes was carried out in buildings that have vertical geometric irregularities by varying the dimensions and reinforcement of the columns. The behavior of the building structure produces structural responses in the form of base shear, fundamental period, displacement and story drift. Analysis of earthquake using dynamic analysis of response spectrum based on SNI 1726 2019 with the help of ETABS software version 9.7.4. The results of this research indicate that the variation of column dimensions and column reinforcement in buildings with irregular vertical geometry reduces the stiffness of the building thereby reducing the forces in the structure, increasing the fundamental period, reducing the base shear force, increasing the displacement and the story drift.